2022
DOI: 10.3390/ijerph19148365
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Literacy in German Skin Cancer Patients

Abstract: The global incidence of skin cancer has steadily increased in recent years, and malignant melanoma still has one of the fastest-growing incidence rates among all malignant tumors in the western world. Thus, newly diagnosed patients have an increased need for health information concerning their disease. Using a standardized questionnaire, our study aims to investigate our patients’ primary sources of health-related information as well as their self-proclaimed eHealth literacy. We received 714 questionnaires. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…The study corresponded with the study of Milne et al 26 which has indicated that cancer patients high eHealth literacy correlated with the level of education received. This also aligns with previous research, 27 , 28 which has shown that patients with lower levels of education have greater difficulties in comprehending and utilizing eHealth information. These findings suggest that targeted and personalized educational interventions are needed to improve eHealth literacy among cancer patients, particularly those with lower levels of education.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study corresponded with the study of Milne et al 26 which has indicated that cancer patients high eHealth literacy correlated with the level of education received. This also aligns with previous research, 27 , 28 which has shown that patients with lower levels of education have greater difficulties in comprehending and utilizing eHealth information. These findings suggest that targeted and personalized educational interventions are needed to improve eHealth literacy among cancer patients, particularly those with lower levels of education.…”
Section: Discussionsupporting
confidence: 91%
“…The study corresponded with the study of Milne et al 26 which has indicated that cancer patients high eHealth literacy correlated with the level of education received. This also aligns with previous research, 27,28 which has shown that…”
Section: Principal Findingssupporting
confidence: 93%
“…For example for those with a darker skin type, as multiple studies have demonstrated that algorithms tend to underperform due to bias in training data, 25 , 26 or for patients with low technological literacy who have difficulties using smartphones. 27 , 28 , 29 Additionally, some lesions might even never be suitable for this technology, such as lesions that are covered by hair, lie in a body fold and are difficult to photograph or where algorithms struggle with noise removal. 15 , 16 , 30 , 31 It is therefore important to be aware of these limitations and search for solutions through both algorithm improvements and ensuring that healthcare remains accessible to all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is minimal literature exploring user suitability for digital dermatology care. eHealth literacy has, however, previously been assessed by Stege et al [13] in a population of patients with skin cancer. Stege et al [13] report greater eHealth literacy in younger, well-educated participants, though we are unable to determine from their data the proportion of their participants who are at risk of digital exclusion.…”
Section: Principal Findingsmentioning
confidence: 99%
“…eHealth literacy has, however, previously been assessed by Stege et al [13] in a population of patients with skin cancer. Stege et al [13] report greater eHealth literacy in younger, well-educated participants, though we are unable to determine from their data the proportion of their participants who are at risk of digital exclusion. Our comparative lack of demographic trends may be due to the broad inclusion criteria for the cluster analysis and limited sample size.…”
Section: Principal Findingsmentioning
confidence: 99%